Complexity of urban ecosystems: the contribution of human ecology - Roderick J. Lawrence (Environmental Management Society, Malaysia, 2009)
Urban ecosystems are complex with many material and non-physical constituents. They are not structured within traditional disciplines and professional sectors. Therefore, they ought to be considered in terms of the multiple factors that influence both the structure and functioning of these ecosystems. An ecological perspective recognizes that behavioural, biological, cultural, economic, social, physical and political factors need to be considered if a comprehensive understanding of urban ecosystems is to complement disciplinary and sector-based interpretations. Key concepts and principles of human ecology are applied in this paper to help achieve this objective